2000
DOI: 10.1042/0264-6021:3450099
|View full text |Cite
|
Sign up to set email alerts
|

Two zebrafish (Danio rerio) antizymes with different expression and activitiesThe nucleotide sequence data reported will appear in DDBJ, EMBL and GenBank Nucleotide Sequence Databases under the accession numbers AB017117 (AZS) and AB017118 (AZL).

Abstract: Cellular polyamines are regulated by a unique feedback mechanism involving ornithine decarboxylase (ODC) antizyme. The synthesis of mammalian antizyme requires a programmed translational frameshift event induced by polyamines. Antizyme represses ODC, a key enzyme for polyamine synthesis, through accelerating enzyme degradation by the 26 S proteasome. Antizyme also inhibits the cellular uptake of polyamines. In the present study we isolated two distinct zebrafish (Danio rerio) antizyme cDNA clones (AZS and AZL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Two paralogs of antizymes in zebrafish ( Danio rerio ), AZS and AZL, are also ubiquitously expressed although each shows a distinct expression profile in developing embryos (72). The antizyme homolog in Drosophila is also ubiquitously expressed (73), and probably in other animals also.…”
Section: Antizyme Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two paralogs of antizymes in zebrafish ( Danio rerio ), AZS and AZL, are also ubiquitously expressed although each shows a distinct expression profile in developing embryos (72). The antizyme homolog in Drosophila is also ubiquitously expressed (73), and probably in other animals also.…”
Section: Antizyme Typesmentioning
confidence: 99%
“…One is known as ‘1S’ and the other as ‘1L’ (though S and L originally referred to short and long, analysis of further sequences showed that the length difference between the paralogous pair in a particular species maybe as small as 1 amino acid, and also that the S ortholog in one species can be longer than the L form of another species). Orthologs of antizyme 1S have the same arrangement of AUGs in ORF1 as higher vertebrates while orthologs of antizyme 1L usually have three in-frame AUGs in their ORF1 (99,100). …”
Section: ′ Conservation and Frameshift Stimulatorsmentioning
confidence: 99%
“…To date, we have reviewed each of the three antizyme genes in 91 vertebrate organisms. This review included two antizyme 1 paralogs ( oaz1a/azs and oaz1b/azl ) in fish ( 23 ) and the novel, retina-specific antizyme ( oaz2b/azr ) in zebrafish ( 24 ). The GeneID and RefSeq identifiers and other related information for the genes reviewed in different organisms are provided in Supplemental Table S1, and general statistics of the data reviewed are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%